3 or 4 years for Anesthesia Residency Program? How to approach the discussion in terms of competency‐based education☆. Issue 2 (April 2017) - Olmos‐Vega, Francisco Manuel; Bonilla‐Ramirez, Antonio José
ABSTRACT : Faced with the dilemma of extending the anesthesiology residency from 3 to 4 years, there have been several arguments for and against. However, the starting point of the discussion must be redesigning the national program curricula to move away from a fixed‐time training and variable competencies, to a competency‐based model; i.e., fixed competencies and variable time frames. ¿3 o 4 años de residencia en anestesiología?: cómo plantear la discusión en términos de educación basada en competencias: RESUMEN: Ante la disyuntiva de prolongar la duración de la residencia en anestesiología de 3 a 4 años se han esgrimido varias razones de lado y lado. Sin embargo, la discusión debe partir de un rediseño curricular de los programas nacionales para dar el paso de un entrenamiento de tiempo fijo y competencias variables a el paradigma de educación basada en competencias, es decir, competencias fijas y tiempo variable.